Penerapan Model Problem Based Learning (PBL) Untuk Meningkatkan Hasil Belajar Siswa Pada Mata Pelajaran IPS di Sekolah Dasar - Yossi Desvariana (Social, Humanities, and Educational Studies (SHEs): Conference Series, 2020)
Social Sciences (IPS) is one of the subjects in the curriculum in SD/MI. Social studies learning does not only require students to understand what has been learned, but also must be able to provide real social examples in the community around the material presented. The implementation of social studies learning in elementary schools is still not optimal because in the learning process teachers have not used a variety of effective learning models to attract students' attention. One of the learning models that can activate students is the Problem Based Learning model. This learning model presents a real problem for students as the beginning of learning then solved through investigation and applied using a problem solving approach. This study aims to understand the application of the Problem Based Learning learning model to improve student learning outcomes in social studies learning in elementary schools. So it can be concluded that teachers should apply innovative learning models in the social studies learning process such as using the Problem Based Learning model.